The book thief - Zusak, Markus; Corduner, Allan (New York : Random House/Listening Library, 2006)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors.
Compact disc.
Unabridged.
Read by Allan Corduner.
Keywords: Books and reading -- Juvenile fiction; Storytelling -- Juvenile fiction; Death -- Juvenile fiction; Jews -- Germany -- History -- 1933-1945 -- Juvenile fiction; World War, 1939-1945 -- Jews -- Rescue -- Juvenile fiction; Germany -- History -- 1933-1945 -- Juvenile fiction; Audiobooks